Association of immune‐related pneumonitis with clinical benefit of anti‐programmed cell death‐1 monotherapy in advanced non‐small cell lung cancer. (13th June 2021) - Ono, Kana; Ono, Hirotaka; Toi, Yukihiro; Sugisaka, Jun; Aso, Mari; Saito, Ryohei; Kawana, Sachiko; Aiba, Tomoiki; Odaka, Tetsuo; Matsuda, Suguru; Saito, Shin; Narumi, Akane; et al.
Abstract: Background: The association between the development of checkpoint inhibitor pneumonitis (CIP) with tumor response and survival has remained unclear so far. The aim of the present study was to evaluate the association between CIP and the clinical efficacy of anti‐programmed cell death‐1 antibody in patients with advanced non‐small cell lung cancer (NSCLC). Methods: Between January 2016 and August 2019, 203 advanced NSCLC patients were administered with nivolumab or pembrolizumab. Comparisons were made between patients with and without CIP. We evaluated the time‐to‐treatment failure (TTF), progression‐free survival (PFS), and overall survival (OS). Results: CIP was observed in 28 (14%) patients. CIP was associated with a longer PFS (18.9 months [95% confidence interval, CI: 8.7 months–not reached] vs. 3.9 months [95% CI: 3.4–5.1 months, p  < 0.01]) and longer OS (27.4 [95% CI: 20.7 months–not reached] vs. 14.8 months [95% CI: 11.2–17.9 months, p  = 0.003]). Most patients discontinued the immune checkpoint inhibitor (ICI) treatment when they developed CIP. Seven patients (25%) lived for more than 300 days from treatment discontinuation and did not show any long‐term tumor growth after treatment discontinuation. Conclusion: CIP was associated with prolonged PFS and OS. Additionally, 25% of CIP patients did not show any tumor growth for long periods after treatment discontinuation. Careful management of CIP can help in obtaining the best clinical efficacy from anti‐PD‐1 antibody. Abstract : This study aimed to evaluate the association between checkpoint inhibitor pneumonitis (CIP) and the clinical efficacy of anti‐programmed cell death‐1 monotherapy in patients with advanced non‐small cell lung cancer (NSCLC). CIP was associated with a longer PFS (18.9 months vs. 3.9 months, p  < 0.01) and longer OS (27.4 vs. 14.8 months, p  = 0.003), and 25% of CIP patients did not grow tumors long after treatment was discontinued. We believe that cautious management of irAEs (especially early detection and treatment) can facilitate achieving the maximum clinical benefit from nivolumab or pembrolizumab monotherapy.